“Concert” or Solo Gig? Where the NLRB Went Wrong When it Linked in to Social Networks - Andrew Metcalf (Washington University Law Review, 2013)
This Note argues that some of the recent social media decisions by Administrative Law Judges (ALJs) and the National Labor Relations Board (NLRB) may extend section 7‘s protection of concerted activity beyond what precedent allows.32 Furthermore, it proposes that even where the activity is concerted and for mutual aid or protection, the NLRB should not apply section 7 protection to employee social network posts that tarnish the employer‘s public image by disseminating details about workplace problems on the Internet. The Supreme Court has suggested that ―even when concerted activity comes within the scope of the ̳mutual aid or protection‘ clause, the forms such activity permissibly may take may well depend on the object of the activity. In the social networking cases, the Board and courts would best effectuate the purpose of the National Labor Relations Act (NLRA), while allowing employers to control their public image, by protecting only employees‘ online statements that are communicated privately or that do not disparage the employer. Part I provides a general history of the NLRA and an overview of recent social networking cases that have been decided by ALJs. Part II examines the definition of concerted activity and the challenges for parties who contend that their individual social network activity was concerted. Part III discusses the ―mutual aid or protection‖ requirement. Part IV suggests that in deciding whether to grant employees section 7 protection, the NLRB should adopt a balancing test that would consider the form of the protest against the object of the activity before extending protection.
Keywords: Hispanics United of Buffalo; NLRB; NLRA; facebook